2015
DOI: 10.1002/aenm.201501640
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Backscattering Effect in High‐Efficient Organic Photovoltaic Devices

Abstract: A universal strategy for efficient light trapping through the incorporation of gold nanorods on the electron transport layer (rear) of organic photovoltaic devices is demonstrated. Utilizing the photons that are transmitted through the active layer of a bulk heterojunction photovoltaic device and would otherwise be lost, a significant enhancement in power conversion efficiency (PCE) of poly[N‐9′‐heptadecanyl‐2,7‐carbazole‐alt‐5,5‐(4′,7′‐di‐2‐thienyl‐2′,1′,3′‐benzothiadiazole)]:phenyl‐C71‐butyric acid methyl es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 60 publications
2
47
0
1
Order By: Relevance
“…[199][200][201][202][203][204][205][206][207][208][209][210] Plasmonic enhancement is achieved mainly through three mechanisms, including far-field scattering, near-field enhancement, and charge carrier or resonant energy transfer. [206] Subwavelength-sized nanoparticles of noble metals such as Au and Ag can exhibit strong localized surface plasmon resonances (LSPRs) at the wavelengths range from UV, visible to near infrared (NIR), depending on the kind of material, their size, particle aspect ratio, and the environment.…”
Section: Plasmonic Effect For Performance Enhancement In Pec Water Spmentioning
confidence: 99%
“…[199][200][201][202][203][204][205][206][207][208][209][210] Plasmonic enhancement is achieved mainly through three mechanisms, including far-field scattering, near-field enhancement, and charge carrier or resonant energy transfer. [206] Subwavelength-sized nanoparticles of noble metals such as Au and Ag can exhibit strong localized surface plasmon resonances (LSPRs) at the wavelengths range from UV, visible to near infrared (NIR), depending on the kind of material, their size, particle aspect ratio, and the environment.…”
Section: Plasmonic Effect For Performance Enhancement In Pec Water Spmentioning
confidence: 99%
“…[ 174 ] Complementary to forward scattering by localized SPRs, plasmonic backscattering effects are also verifi ed to effectively increase optical absorption in OPVs. As Kymakis et al demonstrated, [ 175 ] effi cient light trapping by incorporating Au nanorods in the TiO 2 EEL of OPVs was achieved with a PCE improvement ratio of 18% (Figure 12 f). A dual-plasmonic effect was claimed to be responsible for the broad and uniform increase in EQE spectra: the far fi eld scattering of Au nanorods inside the TiO 2 layer and the near fi eld SPR of the nanorods that penetrated into the photoactive layer.…”
Section: Modifi Cation Of Charge Extraction Layersmentioning
confidence: 76%
“…Strong far-field scattering can increase the absorption efficiency in thin film solar cells by exploiting the effect of total internal reflection. This has been already demonstrated in amorphous-silicon-based thin-film solar cells [11] and in organic solar cells [12]. Moreover, the high local fields in the vicinity of plasmonic nanoparticles overlap not only with metal but also with the surrounding absorbing matter resulting in increased absorption, A.…”
Section: Introductionmentioning
confidence: 78%